Analyzing the efficacy of outcome-based education in Kurikulum Merdeka: A literature-based perspective - R. Risna (Curricula: Journal of Curriculum Development, 2023)
This study analyzes the effectiveness of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective. Through a literature review, this effectiveness analysis method combines theoretical and practical aspects to better understand the contribution of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective. Students can improve their reading comprehension skills by developing literary skills, interpreting metaphor and symbolism, and appreciating literary style and structure. This analysis concludes that Results-Based Education in Kurikulum Merdeka when viewed from a literature-based perspective, can increase students' understanding of literary works, develop literary skills, broaden appreciation of literary diversity, and encourage creativity in writing literature. To maximize the effectiveness of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective, strong integration between literature and results-based learning, development of critical thinking skills through literature, an emphasis on appreciation of literary diversity, and an emphasis on creativity in writing literature can be implemented.